Edaravone Improves Streptozotocin-Induced Memory Impairment via Alleviation of Behavioral Dysfunction, Oxidative Stress, Inflammation, and Histopathological Parameters - Mahdieh Anoush; Soroush Bijani; Fatemeh Moslemifar; Fatemeh Jahanpour; Ali Kalantari-Hesari; Mir-Jamal Hosseini (Behavioural Neurology)
Alzheimer’s disease (AD), as the main cause of dementia, has a progressive and neurodegenerative pattern with number of cases increasing over the next decades. Therefore, discovering an effective treatment with the ability to invert memory impairment and pathophysiological events of AD seems to be required. The present study performed to investigate the probable effects of Edaravone (EDV) in AD-like disorder induced by intracerebroventricular streptozotocin (ICV-STZ) administration in mice. This study also compares the two different methods of ICV-STZ in the memory impairment induction. NMRI male mice were administrated with 3 mg/kg of STZ for two times during 48 hours span, and after 24 hours, animals were treated with EDV (5 and 10 mg/kg), Donepezil, and Memantine for 14 days. After behavioral tests regarding memory and cognitive function, animals were sacrificed, and the hippocampi were utilized for further analyses. Our results demonstrated that administration of STZ induced memory impairment in the Morris water maze (MWM) test and decreased the discriminative factor in novel object recognition (NOR). The biochemical output shows a significant decrease in ferric reducing antioxidant power (FRAP) and glutathione (GSH) levels followed by increase in malondialdehyde (MDA) and protein carbonylation (PCO) levels. The output showed no difference between the patterns of AD-like disorder induction. Following our treatment groups, administration of EDV (5 and 10 mg/kg), Donepezil, and Memantine significantly improved memory performance and discriminatory behavior. Aforementioned treatments managed to improve FRAP and GSH content of hippocampus, while significantly attenuating MDA, PCO, and nitric oxide overproduction. In addition, no significant difference has been observed between the effect of 5 and 10 mg/kg EDV application. It was supposed that EDV managed to ameliorate memory dysfunction, discriminatory behavior, oxidative stress, and cellular antioxidant power in a dose-independent pattern in mice.